THE EFFECT OF CONTEXT, INFERENCE, AND INTERCULTURAL COMMUNICATION ON THE LANGUAGE USE IN CROSS-CULTURAL COMMUNICATION THROUGH THE KNOWLEDGE OF PRAGMATIC COMPETENCE (Intent Research Scientific Journal, 2024)
The goal of the study is to use pragmatic competence to explain the effect of context, inference, and multicultural communication on language in cross-cultural communication. The researchers examined pragmatic competence and the impact of intercultural communication, context, and inference on language.The qualitative exploratory analysis is used. The study investigates the value of pragmatic competence in effective communication. The study also investigates pragmatic competence, and its components such as context, inference and implication, cultural sensitivity, courtesy and social refinements, and the role that education plays in fostering these abilities. In addition, the significance of context, inference, implication, politeness, cultural sensitivity, and social graces in cross-cultural communication are investigated too. The study also shows the importance of education ' s contribution to the development of pragmatic competence.